2017
DOI: 10.3390/ma10070831
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3D-Printed Polycaprolactone Scaffolds Coated with Freeze-Dried Platelet-Rich Plasma for Bone Regeneration

Abstract: Three-dimensional printing is one of the most promising techniques for the manufacturing of scaffolds for bone tissue engineering. However, a pure scaffold is limited by its biological properties. Platelet-rich plasma (PRP) has been shown to have the potential to improve the osteogenic effect. In this study, we improved the biological properties of scaffolds by coating 3D-printed polycaprolactone (PCL) scaffolds with freeze-dried and traditionally prepared PRP, and we evaluated these scaffolds through in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 54 publications
2
101
0
Order By: Relevance
“…The absorbance measurements were performed at a wavelength of 450 nm using a microplate reader. 12,23,[27][28][29][30] In vivo studies Surgical procedure. A total of 15 adult New Zealand white rabbits weighing about 2.5 kg of either gender were obtained from West China Animal Centre of Sichuan University.…”
Section: Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorbance measurements were performed at a wavelength of 450 nm using a microplate reader. 12,23,[27][28][29][30] In vivo studies Surgical procedure. A total of 15 adult New Zealand white rabbits weighing about 2.5 kg of either gender were obtained from West China Animal Centre of Sichuan University.…”
Section: Characterizationmentioning
confidence: 99%
“…CTAn and CT Vol Realistic 3D Visualization soware packages were used for image processing during CT reconstructions and creation and visualization of the 3D representations. 26,30 Histological staining. The harvested scaffold samples were xed with 4% paraformaldehyde solution and decalcied using Shandon TBD-2 Decalcier for 14 days.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies in cranial and mandibular defects showed that the addition of PRP to xenografts, alloplastic materials or scaffolds improved bone formation compared to the use of the grafts/scaffolds alone (Aghaloo, Moy & Freymiller, ; Chen, Lu, Liu, Tang & Zhang, ; El Backly, Zaky, Canciani, Saad & Eweida, ; Hirota, Matsui, Mizuki, Kishi & Watanuki, ; Kim, Kim, Kim, Lim & Kim, ; Li, Chen, Wei, Hao & Wang, ; Penteado, Colombo, Penteado, Assis & Gurgel, ; Schlegel et al., ), other studies did not confirm these findings (DeNicolo, Guyton, Cuenin, Hokett & Sharawy, ; Faratzis, Leventis, Chrysomali, Khaldi & Eleftheriadis, ; Plachokova, Dolder, Stoelinga & Jansen, ; Rocha, Ramos, Batista, Zanetta‐Barbosa & Ferro, ; Wiltfang et al., ) or showed that the use of MSCs in conjunction with bone substitutes could enhance bone regeneration more than PRP (Khojasteh, Eslaminejad & Nazarian, ). It was also shown that adding PRP to GBR (Kazakos, Lyras, Thomaidis, Agrogiannis & Botaitis, ) or to BMP (Ferraz, Schellini, Schellini, Pellizon & Hirai, ) did not accelerate the bone formation process.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic or natural animal-free polymers such as cellulose (Huber et al, 2012;Hickey et al, 2018), chitin/chitosan (Jayakumar et al, 2011), alginate (Lee and Mooney, 2012), recombinant silk (Widhe et al, 2010), PLA (Serra et al, 2013), and PCL (Li et al, 2017) provide low cost, consistent and tunable scaffolds. In this concise review we have chosen to focus on chitin/chitosan, cellulose (bacterial and plant), and recombinant collagen and their use in tissue engineering and potential applications in cellular agriculture.…”
Section: Introductionmentioning
confidence: 99%